Exploring biological efficacy of novel benzothiazole linked 2, 5-disubstituted-1, 3, 4-oxadiazole hybrids as efficient α-amylase inhibitors: Synthesis, characterization, inhibition, molecular docking, molecular dynamics and Monte Carlo based QSAR studies. (November 2021) - Duhan, Meenakshi; Kumar, Parvin; Sindhu, Jayant; Singh, Rahul; Devi, Meena; Kumar, Ashwani; Kumar, Ramesh; Lal, Sohan
Abstract: In an effort to explore a class of novel antidiabetic agents, we have made an effort to synergize the α-amylase inhibitory potential of 1, 3-benzothiazole and 1, 3, 4-oxadiazole scaffolds by combining the two into a single structure via an ether linkage. The structure of synthesized benzothiazole clubbed oxadiazole derivatives are established by different spectral techniques. The synthesized hybrids are evaluated for their in vitro inhibitory potential against α-amylase. Compound 8f is found to be the most potent with a significant inhibition (87.5 ± 0.74% at 50 μg/mL, 82.27 ± 1.85% at 25 μg/mL and 79.94 ± 1.88% at 12.5 μg/mL) when compared to positive control acarbose (77.96 ± 2.06%, 71.17 ± 0.60%, 67.24 ± 1.16% at 50 μg/mL, 25 μg/mL and 12.5 μg/mL concentration). Molecular docking of the most potent enzyme inhibitor, 8f, shows promising interaction with the binding site of biological macromolecule Aspergillus oryzae α-amylase (PDB ID: 7TAA ) and human pancreatic α-amylase (PDB ID: 3BAJ ). To a step further, in-depth QSAR studies show a significant correlation between the experimental and the predicted inhibitory activities with the best R validation 2 = 0.8701 . The developed QSAR model can provide ample information about the structural features responsible for the increase and decrease of inhibitory activity. The mechanistic interpretation of the structure-activity relationship (SAR) is done with the help of combined computational calculations i.e. molecular docking and QSAR. Finally, molecular dynamic simulations are performed to get an insight into the binding mode of the most potent derivative with α-amylase from A. oryzae (PDB ID: 7TAA ) and human pancreas (PDB ID: 3BAJ ). Graphical abstract: Image 1 Highlights: 22 derivatives of 2, 5-disubstituted-1, 3, 4-oxadiazole hybrids are synthesized. The synthesized hybrid derivatives are tested for their in vitro inhibitory potential against α-amylase. 8 QSAR models are made using Monte Carlo Algorithm. The mechanistic interpretation of the SAR is done with the help of molecular docking and QSAR. Structural features responsible for the promoter of increase and decrease are also identified.